Motivation and martial arts and combat sports participation: a study protocol (Revista de Artes Marciales Asiáticas, 2019)
Martial arts and combat sports (MA&CS) popularity has been growing, and their associated benefits are widely known. Several studies report psychological benefits related to MA&CS participation. Albeit there is a broad body of research (following the tenets of self-determination theory - SDT) on motivation in sport and exercise, research in MA&CS motivation is scarce or very specific to single disciplines or styles. The objective of this study is to understand the motivational mechanisms for adherence and retention on MA&C practice, to identify differences between MA&CS on participants’ basic psychological needs and the quality of their motivational regulation. Mediation analysis will be conducted to explore the mechanisms of motivation on MA&CS participation.